2006
DOI: 10.1128/mcb.26.2.699-708.2006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of Apoptosis Protein cIAP2 Is Essential for Lipopolysaccharide-Induced Macrophage Survival

Abstract: The cellular inhibitor of apoptosis 2 (cIAP2/HIAP1) is a potent inhibitor of apoptotic death. In contrast to the other members of the IAP family, cIAP2 is transcriptionally inducible by nuclear factor-B in response to multiple triggers. We demonstrate here that cIAP2 ؊/؊ mice exhibit profound resistance to lipopolysaccharide (LPS)-induced sepsis, specifically because of an attenuated inflammatory response. We show that LPS potently upregulates cIAP2 in macrophages and that cIAP2 ؊/؊ macrophages are highly susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
161
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(183 citation statements)
references
References 28 publications
18
161
1
3
Order By: Relevance
“…Another study has shown that cIAP2-deficient mice are highly resistant to LPS-induced shock due to elevated macrophage cell death. 40 We reveal that the underlying mechanism of the findings in these studies may be increased macrophage necroptosis. It has also recently been shown that a mutation in the caspase-11 gene is present cIAP1 À / À mice.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Another study has shown that cIAP2-deficient mice are highly resistant to LPS-induced shock due to elevated macrophage cell death. 40 We reveal that the underlying mechanism of the findings in these studies may be increased macrophage necroptosis. It has also recently been shown that a mutation in the caspase-11 gene is present cIAP1 À / À mice.…”
Section: Discussionmentioning
confidence: 69%
“…C57BL/6J mice and TNFR1/2 À / À (Jax #003243) were obtained at 4-8 weeks of age from Jackson Labs (Bar Harbor, ME, USA). Ageand sex-matched cIAP1 À / À , 44 cIAP2 À / À , 40 and WT C57BL/6J were used for in vivo infection and bone marrow macrophage experiments. xIAP mice were also utilized with age-matched control (C57BL/6J) mice.…”
Section: Methodsmentioning
confidence: 99%
“…20 Likewise, targeted gene disruption of cIAP1 and cIAP2 has not revealed any significant apoptotic phenotypes. 21,22 Although these results could be interpreted to indicate that IAPs do not play a major role for caspase regulation in mammals, a more likely alternative is that their physiological role is masked by functional redundancy. If relatively short-lived organisms such as fruit flies protect themselves against unwanted death using multiple caspase inhibitors (see below; Figure 1), 6,[8][9][10][11][12][13][14][15][23][24][25][26][27][28][29][30][31][32][33][34][35] it would come as a great surprise if mammals would employ fewer safeguards to control caspase activity.…”
Section: Brakes On Death: Caspase Inhibition By Inhibitor Of Apoptosimentioning
confidence: 90%
“…Subsequent overexpression studies showed that cIAP2 has the capacity to activate NF-B (6) and that a RING-deficient version of cIAP1 can cooperate in the activation of NF-B by TRAF2 (3). More recently, however, their involvement in NF-B signaling has been called into question, because studies in cIAP1 and 2 null mice have not supported such a role (20,21). Mice with whole-body deletion of cIAP1 are asymptomatic, and the primary cells tested from these animals display normal TNF␣-induced NF-B activation and are not sensitized to TNF␣-mediated cell death (21).…”
Section: Apoptosis ͉ Receptor Interacting Protein (Rip1)mentioning
confidence: 99%